The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1145/2816455
|View full text |Cite
|
Sign up to set email alerts
|

The Feet in Human--Computer Interaction

Abstract: Foot-operated computer interfaces have been studied since the inception of Human-Computer Interaction. Thanks to the miniaturisation and decreasing cost of sensing technology, there is an increasing interest exploring this alternative input modality, but no comprehensive overview of its research landscape. In this survey, we review the literature on interfaces operated by the lower limbs. We investigate the characteristics of users and how they affect the design of such interfaces. Next, we describe and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(23 citation statements)
references
References 113 publications
1
22
0
Order By: Relevance
“…A range of devices exist for remote pointing but our interest is in computer vision methods that support users in pointer control without the need for mediating devices. Related work generally assumes use of the hands for pointing (e.g., [61,52,5,34,13]) but work in other areas has shown that humans are equally natural at pointing with other parts of their body (literally, from head [45,38] to toe [58]). We reflect this in an approach that is input-agnostic and supports any body movement to be adopted for pointing, contrasting existing systems that are optimised for specific modalities such as tracking of hand gestures [48], head pose [54], or feet [56].…”
Section: Background and Related Workmentioning
confidence: 99%
“…A range of devices exist for remote pointing but our interest is in computer vision methods that support users in pointer control without the need for mediating devices. Related work generally assumes use of the hands for pointing (e.g., [61,52,5,34,13]) but work in other areas has shown that humans are equally natural at pointing with other parts of their body (literally, from head [45,38] to toe [58]). We reflect this in an approach that is input-agnostic and supports any body movement to be adopted for pointing, contrasting existing systems that are optimised for specific modalities such as tracking of hand gestures [48], head pose [54], or feet [56].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Different from earlier explorations of peripheral classroom technologies, this paper particularly explores foot-based interaction as a style for peripheral interfaces. Footbased interaction has been studied since the very beginning of the HCI realm [28], and has before that been used as a supportive or secondary modality to manual tasks of people such as potters, organists, or drivers. Because humans have highly developed abilities to manipulate artifacts by hand, feet are not often the first choice for performing human-computer interaction.…”
Section: Related Workmentioning
confidence: 99%
“…In the area of peripheral interaction, Probst [31] explored foot kicking and rolling as interaction styles in the context of desktop computing (in sitting posture). Velloso et al [28] presented a com-prehensive review of foot based HCI, in which they also pointed out that since a lot of work of this area has been done in laboratory settings, more field deployments for extended periods of time are still needed. The work presented in this paper contributes a field deployment of a foot-based interface specifically aimed at shifting some of teachers' interactions with the interactive whiteboard to the periphery of attention.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These, including touch and mid-air gestures, are the most popular means of interaction with the available surfaces, such as tablets, and they have been shown adequate for all kinds of users, from kindergartners (Nacher et al, 2014(Nacher et al, , 2015 to the elderly (Loureiro and Rodrigues, 2011). Foot-based interactions, on the other hand, have been less explored and rely on using one's own feet to interact, normally, with a surface on the floor (Law et al, 2009;Leo and Tan, 2010;Velloso et al, 2015). Surface-based interactions are based on manipulating the screen's device to trigger a reaction on itself, for example, by making a gesture with it (Merrill et al, 2007) or bumping two devices together (Hinckley, 2003;Schmidt et al, 2012).…”
Section: Interaction Instrumentsmentioning
confidence: 99%